Contested narratives: a qualitative analysis of abortion testimonies in Louisiana legislature - Silva, Martha; Stolow, Jeni; Burdick, Micki; Mercieca, Amy (Frontiers in Global Women's Health, 2025)
IntroductionFollowing the Supreme Court's 2022 decision in Dobbs v. Jackson Women's Health Organization, Louisiana enacted a “trigger law” banning nearly all abortions. Attempts to reform existing restrictive legislation so as to allow for abortions under exceptions have been unsuccessful to date. This study aims to describe how abortion discourse is framed in public testimony around House Bill 346 in the 2023 Louisiana legislative session, which attempted to pass an abortion exception for pregnancy in the case of rape or incest.MethodsWe conducted a conventional qualitative content analysis utilizing a rhetorical lens, using testimony transcripts from the May 10, 2023, Louisiana Administration of Criminal Justice Committee hearing. An iterative coding approach allowed us to categorize salient themes, language patterns, speaker characteristics, emotional tones, and rhetorical strategies. Demographic characteristics were ascribed to speakers based on perceived gender and race when not self-identified.ResultsTestimony analysis revealed four primary themes: (1) conflicting representations of abortion, (2) religion's role in shaping discourse, (3) humanization of fetuses vs. pregnant individuals, and (4) debate over available resources for survivors and children. Abortion is represented as being traumatic, adding to the trauma caused by sexual violence, while representing childbearing as healing from trauma. Being conceived as a result of sexual violence is used as an identity marker worthy of protection. Religious rhetoric permeates testimony both in support and in opposition to abortion exceptions, making a “pro-life” stance the starting point for debate. Lastly, we find evidence of dehumanization of survivors' and others' experience.ConclusionsThe testimonies around HB346 expose deeply polarized discourse that reflects moral, religious, and ethical conflicts, as well as mismatched conversations that are unlikely to persuade opposing sides. Addressing these dissonant narratives requires nuanced advocacy strategies and resources to support effective testimony.